Equality in Online Education during COVID-19: Challenging the Educational Needs of Ethnic Minority Students in Vietnam - Duc Huu, Nguyen; Van Tan, Le; Thi Luyen, Phan (Law, State and Telecommunications Review, 2022)
[Purpose] This study analyzes the inequalities of ethnic minority children to adapt to online education. This is also a challenge to the whole education system in Vietnam before the 4th COVID-19 outbreak is considered to have a serious impact on the economy and society of Vietnam. [Methodology/Approach/Design] A case study is conducted in a cross-sectional form with 50 high school students and 10 teachers of the boarding ethnic minority school in Nam Pu district, Dien Bien province of Vietnam. Questions were conducted for students, teachers, and school administrators. [Findings] The lack of WiFi catchers such as laptops, tablets, and smartphones along with poor infrastructure are the main factors affecting the effectiveness of online learning. [Practical Implications] Equality in education is the sustainable development goal adopted by the United Nations in 2015. Geographical differences and economic conditions are factors that directly impact the effectiveness of students’ online learning in the context of COVID-19 19. The Government of Vietnam should have an effective financial policy to provide connectivity for poor students, reducing the gap in access to general education services for online classes that are ethnic minorities.